2008
DOI: 10.1055/s-2008-1067225
|View full text |Cite
|
Sign up to set email alerts
|

Pd-NHC (PEPPSI) Complexes: Synthetic Utility and Computational Studies into Their Reactivity

Abstract: This review concentrates on the results obtained thus far in cross-coupling reactions utilising Pd-PEPPSI-IPr (pre)catalyst. Results from computational studies expose possible factors behind the high reactivity of this complex, as well as mechanistic details for the IPr-Pd-mediated alkyl-alkyl Negishi cross-coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(96 citation statements)
references
References 123 publications
1
83
0
12
Order By: Relevance
“…According to the proposed general catalytic cycle for Pd-PEPPSI-IPr, this homocoupling product originates from the activation of the catalyst. 23 Formation of a black precipitate was observed, presumably palladium metal. …”
Section: Catalytic Applicabilitymentioning
confidence: 99%
“…According to the proposed general catalytic cycle for Pd-PEPPSI-IPr, this homocoupling product originates from the activation of the catalyst. 23 Formation of a black precipitate was observed, presumably palladium metal. …”
Section: Catalytic Applicabilitymentioning
confidence: 99%
“…Pd-PEPPSI-IPr is activated by treatment with MeMgCl to form the active Pd(0) carbene complex, with dissociation of the labile 3-chloropyridine ligand. [18] Oxidative addition of the silylborane to this complex is facilitated by the good s-donor ability of the carbene ligand. Insertion of the alkyne must proceed via a three-coordinated complex, in order to allow coordination of the triple bond to the metal center.…”
Section: Mechanismmentioning
confidence: 99%
“…Reductive elimination, finally, is facilitated by bulky ligands, such as PEPPSI-IPr. [18] The success of the carbene ligand is probably the result of these elementary catalytic steps being favored.…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of this type are rare as specially designed, highly active catalysts are typically required to couple unactivated alkyl fragments efficiently, [12] with the trade-off that discrimination between C alkyl ÀBr and C alkyl ÀCl bonds is now less chemoselective. For example, we have shown that NHC-Pd catalysts (NHC = N-heterocyclic carbene), generated in situ from either an imidazolium salt [13] or a pre-catalyst, [14] namely [Pd-PEPPSI-IPr] (1), [15] can effectively couple both unactivated primary C alkyl ÀBr and C alkyl ÀCl bonds in the Negishi reaction at room temperature. [16] During the course of these studies, however, we discovered a unique property that allowed us to chemoselectively couple C alkyl À Br bonds in the presence of C alkyl À Cl bonds with alkylzinc reagents: that is, solvent polarity.…”
mentioning
confidence: 99%